1991
DOI: 10.1111/j.1365-2826.1991.tb00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Implants in the Hypothalamus Inhibit Prolactin Surges During Pregnancy and Alter Prolactin Release in Response to Dopamine Receptor Blockade

Abstract: The purpose of this study was to determine whether prolactin (PRL) could exert a negative feedback on it's own secretion during pregnancy and following ovariectomy, and to determine t h e possible mechanism by which this feedback acts. Implantation of ovine PRL into t h e arcuate nucleus-median eminence area of t h e hypothalamus completely inhibited the nocturnal PRL surge during pregnancy in t h e rat, and lowered baseline PRL to almost undetectable levels in t h e ovariectomized rat. W h e n ovariectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Thus, current evidence suggests that one possible function for prolactin release in the male rat is to modulate central neuronal activity of hypothalamic and extrahypothalamic dopaminergic cells. The increase of dopaminergic activity may also serve as a negative feedback mechanism since dopamine inhibits prolactin release [for review, see 39], A negative feedback role for prolactin is supported by the fact that prolactin implants inhibit prolactin surges during pregnancy [40], Prolactin affects several components of the immune sys tem. Injections of prolactin into rats increase antibody production [41,42], This effect may be mediated by acting on T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, current evidence suggests that one possible function for prolactin release in the male rat is to modulate central neuronal activity of hypothalamic and extrahypothalamic dopaminergic cells. The increase of dopaminergic activity may also serve as a negative feedback mechanism since dopamine inhibits prolactin release [for review, see 39], A negative feedback role for prolactin is supported by the fact that prolactin implants inhibit prolactin surges during pregnancy [40], Prolactin affects several components of the immune sys tem. Injections of prolactin into rats increase antibody production [41,42], This effect may be mediated by acting on T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Arbogast and Voogt [14] have shown that pituitary PRL content was lower during the nocturnal PRL surge and higher during the diurnal PRL surge. Substantial decreases in pituitary PRL content were also observed during the preovulatory PRL surge [25,30,42,43] and the estradiol-dependent PRL surge [25,44]. It is possible that the lower PRL response to DOM seen during the nocturnal surge was due to less pituitary PRL available for release, and the higher PRL response to DOM during the diurnal surge was due to more PRL available for release.…”
Section: Discussionmentioning
confidence: 99%
“…Highly developed mammary glands in the cycling rats with Rcho cells indicate the mammotrophic action of the secreted factor. It is possible that PL-I was responsible for the inhibition of PRL synthesis and release, acting like PRL in exerting a negative short-loop feedback on PRL secretion [12,35], although other factors secreted by the Rcho cells could have similar effects. Preliminary experiments from our laboratory show that implantation of recombinant PL-I into the hypothalamus abolishes the nocturnal PRL surge in pregnant rats.…”
Section: Discussionmentioning
confidence: 99%